Non-vitamin K antagonist oral anticoagulants and atrial fibrillation guidelines in practice : barriers to and strategies for optimal implementation - Camm, A. John (2015)
© The Author 2015. Published by Oxford University Press on behalf of the European Society of Cardiology. This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0/), which permits non-commercial re-use, distribution, and reproduction in any medium, provided the original work is properly cited. For commercial re-use, please contact journals.permissions@oup.com